Occurrence and severity of myasthenic crisis in an unselected Turkish cohort of patients with myasthenia gravis - Ozyurt Kose, Selen; Nazli, Ezgi; Tutkavul, Kemal; Gilhus, Nils Erik (Frontiers in Neurology, 2023)
Myasthenia gravis (MG) is a disorder of the neuromuscular junction that can deteriorate into myasthenic crisis, involving weakness of bulbar and respiratory muscles. In this study, we describe the clinical manifestations of myasthenic crisis, identify risk factors, and examine treatments and outcomes. All 95 patients with generalized MG treated at our center during the last 10 years were included in this retrospective study. We collected data from the patients' records, including clinical follow-ups, muscle antibodies, thymic status, and treatments. The characteristics of patients who did and did not experience myasthenic crisis were compared. Features of all myasthenic crises were also assessed. Twelve patients (13%) developed myasthenic crisis during the observation period. Men were more often affected at older ages. Seven patients experienced multiple myasthenic crises. Thymoma increased the risk of a crisis, whereas thymic hyperplasia decreased the risk. Myasthenic crises were more common in the summer months. No patients died during a myasthenic crisis. Risk factors for myasthenic crisis were thymoma, older age, MuSK antibodies, and previous crises. Individualized and active immunosuppressive treatment and optimal intensive care during crises provide a good outcome for patients with generalized MG.